Wars2 is a determinant of angiogenesis - Mao Wang (Nature Portfolio, 2016)
Blood supply to the heart is crucial for cardiac function. Here, the authors show that the mitochondrial tryptophanyl-tRNA synthetase, WARS2, drives blood vessel generation in zebrafish and rats and that inhibition of Wars2 diminishes blood vessel growth both within and outside in the heart, suggesting a new target for manipulating angiogenesis.